Geographical distribution of Lasaia Bates, 1868 (Lepidoptera: Riodinidae) across the biogeographical provinces of Mexico - Arellano-Covarrubias, Arturo; Trujano-Ortega, Marysol; Luis-Martínez, Armando; Luna-Reyes, Mercedes; Llorente-Bousquets, Jorge (Zootaxa, 2019)
Riodinidae are one of the most diverse families of Lepidoptera, mainly in the Neotropical region; however, their biology, ethology, taxonomy, systematics, and biogeography are poorly known. In Mexico, the regional and local distributions of the family are still incomplete. We review the distributional data of the genus Lasaia Bates (Lepidoptera: Riodinidae), based on records from four national and seven international collections. We record five species and seven subspecies in Mexico, with 2722 records, distributed in 314 localities of 24 states. The states with higher species richness are Chiapas, Oaxaca, and Veracruz; also, the genus was recorded in 11 of the 14 biogeographical provinces of Mexico. The tropical semi-deciduous and deciduous forests, below of 1000 m a.s.l., contain most of the diversity of Lasaia. Historical data are crucial for the study of local and regional diversity and ecological patterns at large temporal scales. Data presented here show the morphological and ecological variation of Lasaia over the last 80 years, mostly from the XX century when anthropogenic disturbances were intensified. This kind of studies is the first step in recording the historical distribution of these taxa, which will lead to more complex analyses on distribution range shifts, their causes and consequences.